The validity of resonant field imaging (RFI) frequency counter in measuring psychological stress levels in comparison with clinical and biological stress markers / Nurul Iwani Abdullah - Abdullah, Nurul Iwani (2015)
Traditionally, self-administered questionnaires and measurement of cortisol have been widely used in the evaluation of psychological stress. Nevertheless, these approaches are rather time consuming, need full individuals’ cooperation and raise a stigma issue. As bioenergy field of the human body has been claimed as an important parameter of mental health, this study attempted to validate the Resonant Field Imaging (RFI) frequency counter in measuring psychological stress levels via the measurement of bioenergy frequency. A cross-sectional randomized study was therefore conducted on 141 healthcare workers in Faculty of Medicine, Universiti Teknologi MARA (UiTM) Sungai Buloh Campus. The bioenergy frequency of subjects was measured at the frontal area using RFI frequency counter, followed by the measurement of salivary cortisol levels and the evaluation of psychological stress, anxiety and depression symptoms via General Health Questionnaire-12 (GHQ-12), Kessler Psychological Distress Scale (K10) and Hospital Anxiety and Depression Scale (HADS). The prevalence of psychological stress determined by GHQ-12, K10 and HADS scores were found to be 38.3%, 48.2%, 47.5% and 20.6%, respectively. Both bioenergy frequencies and salivary cortisol were revealed to be significantly different among gender and educational levels (p<0.05). Psychological stress measured via GHQ-12, K10 and HADS was significantly associated with factors such as gender, age, educational levels and marital status (p<0.05). Further analysis revealed that the main risk factors for stress were being a female, single and working in the clinical field. A significant difference in bioenergy frequencies was also found between the groups of stressed and non-stressed subjects (p<0.05). There were weak correlations reported between bioenergy frequency and K10 and HADS-Anxiety subscale. The RFI frequency counter has moderate sensitivity and specificity with moderate Positive Predictive Value (PPV) and Negative Predictive Value (NPV). In conclusion, the RFI frequency counter could serve as a potential screening tool in detecting individual with stress.